Quality and perceived value in career guidance e-services. Issue 1 (14th September 2018) - Cobelli, Nicola; Bonfanti, Angelo; Cubico, Serena; Favretto, Giuseppe
Abstract : Purpose: This paper aims to empirically examine career guidance services in terms of e-service quality, information quality and perceived value. It specifically examines students' perceptions of quality to explore the effects of e-service quality and information quality on perceived value. Design/methodology/approach: Students from the University of Verona participated in a quantitative survey, and 119 questionnaires were collected to assess the perceptions of respondents on e-service quality, information quality and perceived value about the career guidance e-service. Findings: The results indicate that students perceive high value for the career guidance services; the perceived value depends on both service quality of the e-platform and information quality of the report; and efficiency is the most important dimension of e-service quality, while adequacy appears to be the most important dimension of the report. Practical implications: These findings reveal that service organisations such as universities should invest in career guidance services, given that such services are appreciated by students and contribute to reducing the gap between education and job opportunities. In the design phase, service organisations should pay attention to students' career development needs by developing e-platforms that are easy to use, appealing, efficient and with continuous system availability and reports that include relevant, understandable, reliable and adequate information. It is important to provide students with a report after they have completed a questionnaire. Originality/value: To the authors' knowledge, this is the first research empirically evaluating the effects of perceived e-service quality and information quality on perceived value with specific reference to career guidance e-services.